Menggagas Arah Kebijakan Ketenagakerjaan Yang Berkeadilan Demi Mewujudkan Kesejahteraan Pekerja/Buruh - Fitriana, Fitriana (Jurnal Hukum & Pembangunan, 2022)
One of the unsolved economic problems to date is related to the employment aspects. However, Government’s policies to address the problems have not provide a sense of justice for the community. It can be seen from the various actions against Law Number 11 of 2020 on Job Creation. From the drafting until the issuance, the public still rejected the substance of employment provisions because it was considered unfair to workers/laborers. Government policies are needed to protect workers/laborers whose socioeconomic status is weaker than that of employers. This study aims to elaborate issues of injustice that arise as a result of employment regulations under Law Number 11 of 2020 on Job Creation, so that it could be known how the political will of Government should be directed. The result indicates that the political will of Government should prioritize the interest of workers/laborers by fulfilling their human rights, i.e. right to choose employment, to work, and to receive fair and proper remuneration and treatment in employment. With the guarantee of human rights, it would provide a sense of justice in accordance with the values of Pancasila (Indonesia’s five moral principles) and the 1945 Constitution, as well as increase the welfare of workers/laborers as Indonesian citizens.